EFEKTIVITAS PEMBELAJARAN DARING MATA PELAJARAN GEOGRAFI BERBASIS GOOGLE CLASSROOM (GCR) DI SMAN 6 MEDAN - Wahyuni, Yeni Wahyuni; Mariya, Sri (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
During the COVID-19 pandemic, the education system began to look for innovation in the process of teaching and learning activities. One of the learning media during the COVID-19 pandemic is Google Classroom. At SMA Negeri 6 Medan for the first time implementing online learning based on Google Classroom. This study aims to determine the effectiveness of online learning using google classroom in geography lessons at SMA Negeri 6 Medan during the pandemic. This study uses a survey method with a quantitative descriptive approach. The data collection technique used nonprobability sampling method with total sampling technique, the number of samples in this study was taken from the entire population of class X-IIS as many as 72 students. Data collection techniques used are questionnaires and data. The results of this study indicate that the learning effectiveness of class X-IIS students at SMA Negeri 6 Medan using Google Classroom media entered at a very effective level of achievement as many as 42 students from 72 respondents with a percentage of 58.33%, 26 students or 36.11% at the level of achievement. quite effective, 3 students or 4.16% at the ineffective level, and 1 student or 1.4% at the very ineffective level of achievement.